Marker-based analysis of CMS lines for grain and kernel traits in rice hybrids (Bangladesh Journal of Botany, 2022)
The grain size is considered to be one of the complex traits affecting rice yield as it is directed by multifaceted gene combinations. In the present experiment, 34 pollen parents were crossed with four female lines in line × tester matting design and 136 hybrids were generated. Wide phenotypic differences were observed across the hybrids for grain length, grain width and grain length-width ratio. The correlation analysis depicted a strong association among two grain size regulating traits viz., kernel length and kernel length-width ratio. However, kernel width shows negative correlation with these traits and influences the final grain size. The hybrids were also investigated at GS3 and GW8 loci. Gene based markers SF28 and DRR-GL showed strong association with the grain size related traits. The population structure analysis divided the entire material into four subgroups viz., I, II, III and IV with demarcation of long, homozygous and short grain types. The analysis of molecular variance (AMOVA) as well as a pairwise FST analysis indicated significant differentiation of population II as compared to rest of the populations, suggesting that only one among the four subgroups structured significantly different. Marker based evaluation in the present study provides the understanding for selection of suitable candidate markers for obtaining preferred grain shape/size and improving the grain yield through marker-assisted breeding.Bangladesh J. Bot. 51(2): 343-351, 2022 (June)